Time treks - "Nandy, Ashis" (Ranikhet, 2007)
In a world increasingly dominated by a narrow range of ideologies, social ethics and a more humane society can be based on something other than the political and psychological forces that have tried to flatten and homogonize the world over the last two centuries. Time Treks uses the metaphor of the future--imagined utopias, conceptions of cultural possibilities, social critiques of things to come--and redefines the present.
Keywords: India-Politics and government